2020
DOI: 10.1093/femsyr/foaa037
|View full text |Cite
|
Sign up to set email alerts
|

¡Viva la mitochondria!: harnessing yeast mitochondria for chemical production

Abstract: The mitochondria, often referred as the powerhouse of the cell, offers a unique physicochemical environment enriched with a distinct set of enzymes, metabolites, and cofactors ready to be exploited for metabolic engineering. In this review, we discuss how the mitochondrion has been engineered in the traditional sense of metabolic engineering or completely bypassed for chemical production. We then describe the more recent approach of harnessing the mitochondria to compartmentalize engineered metabolic pathways,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…As sites of the βoxidation of fatty acids, peroxisomes can supply ample acetyl-CoA (van der Klei and Veenhuis, 1997). Similarly, mitochondria have nearly 20-30 times higher acetyl-CoA content than the cytosol (Duran et al, 2020). As shown in Figure 2C, rational organelle compartmentalization can greatly improve the utilization efficiency of the acetyl-CoA pools in different organelles (Son et al, 2022a;Lu et al, 2022).…”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 89%
“…As sites of the βoxidation of fatty acids, peroxisomes can supply ample acetyl-CoA (van der Klei and Veenhuis, 1997). Similarly, mitochondria have nearly 20-30 times higher acetyl-CoA content than the cytosol (Duran et al, 2020). As shown in Figure 2C, rational organelle compartmentalization can greatly improve the utilization efficiency of the acetyl-CoA pools in different organelles (Son et al, 2022a;Lu et al, 2022).…”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 89%
“…Unlike monolayers of LDs and peroxisomes, mitochondria are semi-autonomous organelles surrounded by two layers of membrane, with their inner membrane forming mutliple ridges, which can gradually release energy through respiration to meet the requirements of various cell activities. Because acetyl-CoA is an important precursor for terpenoid synthesis, mitochondria have a much higher acetyl-CoA content (nearly 20–30 times higher) than the cytoplasm, which increases the feasibility of mitochondrial compartmentalization for terpenoid synthesis [ 79 , 80 ]. However, IPP and DMAPP, which are synthesized from acetyl-CoA via the MVA pathway, are ATP analogs that are strong inhibitors of the mitochondrial respiratory chain.…”
Section: Compartmentalization Strategies For Effective Synthesis Of T...mentioning
confidence: 99%
“…Most synthetic pathways are targeted to the cytosol due to its big volume, high coverage of metabolic enzymes and metabolites [ 3 , 4 ]. Recent studies have revealed that the yeast mitochondrion could be attractive to produce terpenoids, fumarate, ornithine, and branched-chain alcohols [ 5 7 ]. With the mevalonate pathway and sequential synthetic genes targeted into the mitochondria, researchers have greatly improved the titers of isoprene, patchoulol, valencene, amorphadiene, linalool and santalene [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%